The Rocky Road From Fed-Batch to Continuous Processing With E. coli - Kopp, Julian; Slouka, Christoph; Spadiut, Oliver; Herwig, Christoph (Frontiers in Bioengineering and Biotechnology, 2019)
E. coli still serves as a beloved workhorse for the production of many biopharmaceuticals, as it fulfils essential criteria such as fast doubling times, little risk in contamination and easy upscale. Most industrial process in E. coli are carried out in fed-batch mode. However, recent trends show that biotech industry is moving towards time-independent processing, trying to improve the space-time yield and especially targeting constant quality attributes. In the 1950ies the term “chemostat” was introduced first-time by Novick and Szilard, following up to the pre-work performed by Monod. Chemostat processing resulted in a major hype 10 years after its official introduction. However, enthusiasm decreased as experiments suffered from genetic instabilities and physiology issues. Major improvements in strain engineering and the usage of tuneable promotor systems facilitated chemostat processes. In addition, critical process parameters have been identified and the effects onto diverse quality attributes are understood in much more depth, easing process control. By pooling the knowledge gained throughout the recent years, new applications such as parallelization, cascade processing and population controls are applied nowadays. However, to control the highly heterogeneous cultivation broth to achieve stable productivity throughout long-term cultivations is still tricky. Within this review, we will discuss: - the current state in E. coli fed-batch process understanding and its tech transfer potential to continuous processing - the achievements in continuous Upstream applications with E. coli - the continuous downstream processing of intracellular proteins